Proper Names: Translation Analysis on the Example of “Prince Caspian” - Majcher, Agnieszka Elżbieta Elżbieta (Respectus Philologicus, 2017)
The aim of this paper is to present translation strategies applied in the process of literary translation of proper names. The analysis is carried out on the example of the translation of the novel Prince Caspian by Clive Staples Lewis: into Polish by Andrzej Polkowski and into German by Lena Lademann-Wildhagen. The paper analyses how proper names referring to living creatures, geographical or topographical names were translated. The techniques applied by the two translators were significantly different, from transference, substitution, translation of part of the names, through referring associations with the character’s behaviour or the features of the object, to free translation, limited only by the author’s imagination. All the names were analysed in terms of semantics, morphology, for some the graphemes and phonemes were studied. First, the translation techniques used dealing with proper names were identified. Based on this, the results of the analysis of the selected names from the novel and its translations were presented together with conclusions on their influence on the world depicted in the novels and the impact the differences in translations can have on the reader.
Keywords: Translation Comparison; Literary Translation; Proper Names; Literature for Children